The Effect of Organizational Culture and Readiness to Change on Organizational Entrepreneurship: The Role of Competence - Diwanti, Dyah Pikanthi; Suryanto, Suryanto; Iswati, Sri; Agustina, Tri Siwi; Notobroto, Hari Basuki (Universitas Muhammadiyah Yogyakarta, 2021)
Research aims: The purpose of this study is to reveal/investigate how the organizational culture changes the readiness of human resources through entrepreneurial competence to run an organization. At present, the organization's existence is very competitive with other organizations, making human resources a strategic resource owned by the organization. Therefore, organizations must be able to respond to many events that cause changes in the environmental forces that influence them.Design/Methodology/Approach: The type of research is quantitative research. This study used a questionnaire as the survey technique. The analysis of this research was carried out by conducting a classic assumption test, including the multicollinearity test, heteroscedasticity test, and normality test. Furthermore, the data were analyzed employing multiple linear regression analysis, namely the coefficient of determination test (R2), simultaneous significance test (F), and the test of the significance of individual parameters (T). Intervening variables were tested with path analysis and multiple tests.Research findings: This study’s results revealed that organizational culture, readiness for change, and competence positively and significantly influenced organizational entrepreneurship. Organizational culture and/or readiness for change with competence as an intervening variable also positively and significantly influenced organizational entrepreneurship. Organizational entrepreneurship was influenced by 64% by organizational culture and readiness for change in human resources. Meanwhile, the remaining 36% was explained by other variables outside this study’s model.Theoretical contribution/Originality: The novelty of this research is that organizational entrepreneurship is a reference for business independence in an organization.Practitioner/Policy implication: Organizational entrepreneurship exists in organizations that have business entities for organizational independence.